Removal of metronidazole from simulated wastewater using Fe/C catalyst with a combination of heterogenous Fenton and ozonation - Panandita, Budi Satria; Prasetyo, Imam; Ariyanto, Teguh (Jurnal Rekayasa Proses, 2023)
This study examined roles of iron oxide/porous carbon material (Fe/C) for removing metronidazole in simulated wastewater by adsorption and then followed by a degradation using advanced oxidation process (H2O2, O3 and combination of H2O2/O3). Fe/C was produced by an impregnation of iron oxide precursors during resorcinol-formaldehyde synthesis followed by pyrolysis at 800 °C. For comparison, blank carbon (without iron loading) was also synthesized. The properties of porous carbon were investigated by SEM-EDX and N2-sorption analyzer. Blank carbon and Fe/C featured the specific surface area of 755 m2g-1 and 394 m2g-1, respectively. The loading of iron oxide altered the pore structures of material. The adsorption isotherm data were followed by the Langmuir isotherm model with metronidazole uptake up to 46.07 mg g-1 and 39.97 mg g-1 at 30oC by Fe/C and blank carbon. The degradation study was then carried out with catalyst dosage of 0.1 g/100 mL solution and 120 min reaction time at 30 oC. It is noticeably that, the degradation of metronidazole was better when a combination of H2O2/O3 was employed, compared with an individual of H2O2 or O3. Regarding the stability, Fe/C maintained its high activity upon four consecutive runs.